Walking Human Detection Using Stereo Camera Based on Feature Classification Algorithm of Second Re-projection Error - Wen, Shuhuan; Wang, Sen; Zhang, ZhiShang; Zhang, Xuebo; Zhang, Dan (Frontiers in Neurorobotics, 2019)
This paper presents a feature classification method based on vision sensor in dynamic environment. Aiming at the detected targets, a double-projection error based on orb and surf is proposed, which combines texture constraints and region constraints to achieve accurate feature classification in four different environments. For dynamic targets with different velocities, the proposed classification framework can effectively reduce the impact of large-area moving targets. The algorithm can classify static and dynamic feature objects and optimize the conversion relationship between frames only through visual sensors. The experimental results show that the proposed algorithm is superior to other algorithms in both static and dynamic environments.